Design, synthesis, and investigation of biological activities of new triazole derivatives with antifungal effect - Goktas, Buenyamin; Osmaniye, Derya; Levent, Serkan; Ozkan, Begum Nurpelin Saglik; Ozkay, Yusuf; Kaplancikli, Zafer Asim (Elsevier, 2024)
Fungal infections pose a significant threat to both morbidity and mortality, especially in immunocompromised patients, notably those with conditions such as AIDS. In the last two decades, the incidence of such fungal infections has increased significantly, especially due to Candida species. The increasing incidence of lifethreatening fungal infections has increased the need for new drugs to treat these infections. In this study, 10 novel oxadiazole-triazole hybrid compounds were synthesized. Analysis of the obtained compounds provided by 1H NMR (proton nuclear magnetic resonance), 13C NMR (carbon nuclear magnetic resonance) spectroscopic methods and HRMS (high resolution mass spectrometry) spectrometric method. The inhibition effects of the obtained compounds on the 14 alpha-demethylase enzyme were investigated. Among the synthesized compounds, 4a (contains 4 -methyl substituent), 4c (contains 4-cyano substituent), 4d (contains 4 -nitro substituent), 4e (contains 4-fluoro substituent), 4 g (contains 4-bromo substituent) and 4j (contains 3,4-dichloro substituent) coded compounds were useful against C. parapsilosis strain; Compounds 4c, 4f and 4 g also showed significant inhibitory effect against C. albicans strain. Within the scope of the study, the interactions of 14 alpha-demethylase enzyme active site and our compound were elucidated by molecular modeling and molecular dynamics studies. Binding points were determined by docking studies for the selected compounds in enzyme active site. The strongest interaction with 14 alpha-demethylase enzyme active sites was observed in 4c and 4 g coded compounds.
Keywords: Triazole; 14 alpha-demethylase; Antifungal; Molecular docking; Molecular dynamics